Integrating Data from Multiple Repositories to Analyze Patterns of Contribution in FOSS Projects - Sowe, Sulayman; Cerone, Antonio (Electronic Communications of the EASST, 2010)
The majority of Free and Open Source Software (FOSS) developers are mobile and often use different identities in the projects or communities they participate in. These characteristics not only poses challenges for researchers studying the presence (where) and contributions (how much) of developers across multiple repositories, but may also require special attention when formulating appropriate metrics or indicators for the certification of both the FOSS product and process. In this paper, we present a methodology to study the patterns of contribution of 502 developers in both SVN and mailing lists in 20 GNOME projects. Our findings shows that only a small percentage of developers are contributing to both repositories and this cohort are making more commits than they are posting messages to mailing lists. The implications of these findings for our understanding of the patterns of contribution in FOSS projects and on the quality of the final product are discussed.